Low-angle radar land clutter measurements and empirical models - Billingsley, J. Barrie (William Andrew Pub. : SciTech Pub. ; Institution of Electrical Engineers, 2002)
Provides information on how to design and predict the performance of radars that operate in situations where land clutter is prevalent.
Keywords: Radar -- Interference.; elektronické knihy; electronic books